2020
DOI: 10.3390/d12100393
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Rotifer Diversity in the Chihuahuan Desert

Abstract: Desert aquatic systems are widely separated, lack hydrologic connections, and are subject to drought. However, they provide unique settings to investigate distributional patterns of micrometazoans, including rotifers. Thus, to understand rotifer biodiversity we sampled 236 sites across an array of habitats including rock pools, springs, tanks, flowing waters, playas, lakes, and reservoirs in the Chihuahuan Desert of the USA (n = 202) and Mexico (n = 34) over a period of >20 years. This allowed us to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 136 publications
0
10
1
Order By: Relevance
“…Overall, we found a total number of 39 monogonont rotifer species belonging to 20 genera. Although our study detected a lower number of rotifer species compared to other large-scale studies conducted in Italy, Russia, Poland, Mexico and USA (Braioni & Gelmini, 1983; Kutikova, 1998; Ejsmont-Karabin et al, 2004; Sarma et al, 2021; Brown et al, 2020), our findings suggest that a single sampling of spatio-temporal reservoirs of resting eggs can detect a sufficiently high number of species for diversity assessment and related community/metacommunity analysis. Most importantly, many of the species we detected (25) have not been previously reported from the region, substantially adding to the rotifer diversity in Israel.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Overall, we found a total number of 39 monogonont rotifer species belonging to 20 genera. Although our study detected a lower number of rotifer species compared to other large-scale studies conducted in Italy, Russia, Poland, Mexico and USA (Braioni & Gelmini, 1983; Kutikova, 1998; Ejsmont-Karabin et al, 2004; Sarma et al, 2021; Brown et al, 2020), our findings suggest that a single sampling of spatio-temporal reservoirs of resting eggs can detect a sufficiently high number of species for diversity assessment and related community/metacommunity analysis. Most importantly, many of the species we detected (25) have not been previously reported from the region, substantially adding to the rotifer diversity in Israel.…”
Section: Discussioncontrasting
confidence: 91%
“…Epiphanes brachionus, a recognized indicator species for North America playa habitats (i.e., temporary and semi-permanent water bodies of various sizes; Sublette & Sublette, 1967;Brown et al, 2020), which are comparable in their environmental characteristics (i.e., hydroperiod) to our study system, was found to be extensively distributed in the Mediterranean coast and mountain regions.…”
Section: Discussionmentioning
confidence: 52%
“…Second, even though the regional species accumulation curve suggests that the regional species richness value ( 21) is close to the actual species richness present in the lakes of the PNLM, two methodological concerns must be mentioned. a) Most rotifer studies use nets with smaller mesh size (35-µm or 25-µm, References [56][57][58]) than our (54-µm). b) Rotifer biodiversity studies usually report species from both the littoral and the pelagic zones (e.g., References [7][8][9]12]), while ours included just the pelagic zone.…”
Section: Discussionmentioning
confidence: 99%
“…"Mexico" [18] and Hexarthra n. sp. [19]. In addition, as far as possible, we used published reports of species.…”
Section: Methodsmentioning
confidence: 99%